Pengaruh Current Ratio, Debt To Equity Ratio, dan Return On Assets Terhadap Return Saham (Studi Pada Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Arya Gus Putra; Enny Arita (GLOBAL SCIENTS PUBLISHER, 2025)
The capital market is an important indicator of economic development, where stock price movements are influenced by various fundamental factors of a company. This study aims to examine the effect of the current ratio (CR), debt-to-equity ratio (DER), and return on assets (ROA) on stock returns in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This study is quantitative, using secondary data collected through annual financial report documentation. The study population included 89 energy sector companies listed on the IDX. The sample selection was conducted using a purposive sampling technique, resulting in 30 companies meeting the research criteria. Data analysis used multiple linear regression with hypothesis testing using SPSS software. The results show that the current ratio has a negative and significant effect on stock returns, the debt-to-equity ratio has no significant effect on stock returns, and return on assets has a positive and significant effect on stock returns in energy sector companies. The Adjusted R Square value of 0.389 indicates that the three independent variables are able to explain the variation in stock return changes by 38.9%.